Antithrombotic Regimens in Patients With Percutaneous Coronary Intervention Whom an Anticoagulant Is Indicated: A Systematic Review and Network Meta-Analysis - Wipharak Bunmark; Peerawat Jinatongthai; Peerawat Jinatongthai; Prin Vathesatogkit; Ammarin Thakkinstian; Christopher M. Reid; Christopher M. Reid; Wanwarang Wongcharoen; Nathorn Chaiyakunapruk; Nathorn Chaiyakunapruk; Nathorn Chaiyakunapruk; Nathorn Chaiyakunapruk; et al. (Frontiers Media S.A., 2018)
Background: Patients undergoing percutaneous coronary intervention (PCI) who require anticoagulant therapy are at increased risk of bleeding. The optimal regimen for these patients is uncertain. This study aimed to compare safety and efficacy of antithrombotic regimens used in patients undergoing PCI with concomitant anticoagulant therapy.Methods: A systematic review and network meta-analysis was performed among studies comparing antithrombotic regimens for anticoagulated patients undergoing PCI. The primary outcome of interest was major bleeding. The secondary outcomes were coronary events. The reference intervention was classic triple therapy (aspirin plus clopidogrel plus VKA). Cluster rank incorporating risk (major bleeding) and benefit (all-cause death) was performed to identify the most appropriate regimen(s).Results: There were 3 RCTs (6 interventions) and 29 non-RCTs (8 interventions) that met the inclusion criteria with 22,179 patients. Network meta-analysis of RCTs indicated that dual therapy (DT), either with vitamin K antagonist (VKA) or direct anticoagulant (DOAC) plus an antiplatelet, significantly reduced the risk of major bleeding compared to triple therapy (TT) [pooled RR of 0.51 (0.30-0.87) and 0.68 (0.49-0.94), respectively]. In addition, VKA-DT significantly reduced the risk of all-cause death compared to TT [pooled RR of 0.40 (0.17-0.93)]. Results from network meta-analysis of non-RCT paralleled that of RCTs. No significant differences of coronary events were found.Conclusions: In conclusion, for anticoagulated patients undergoing PCI, dual therapy, either with warfarin or DOAC plus an antiplatelet, should be considered due to its optimal balance on efficacy and safety.